Upaya Guru PAI dalam Menanamkan Sikap Toleransi Antar Peserta Didik - Junaidin Basri; Ahmad Fithron Aula (STAI Al-Musaddadiyah Garut, 2026)
The purpose of this study still has a low tolerance attitude in schools that affects educated people in the community. So it can help to preserve peaceful harmony among tolerant religious people. The purpose of this study is to understand the concept of tolerance in islamic education. The methods used in this study are qualitative methods with a case study approach, data is obtained through: observations, observations, in-depth interviews, and reviewing documents with the participants of his research are the foundation, the principal, teachers and students. The attempts by pai teacher to instill tolerance attitude through classroom and classroom learning and to find out the tolerant student profile in junior high school sexuality. Data was analysed through transkiologic stages, data organization, coding, and triangulation of research found that in general; 1). The learner already knows the concept of tolerance in religious circles among students at the main school of su, with an indicator of students' attitude respecting and honoring the differences between tribes, religions, RACES, and classes, 2). The teacher has made an effort to instill tolerance in the learner by learning inside the class; Silabus, RPS, modules, evaluations, and assessments.3). Found two character profiles of conscientious learners in administering an attitude of tolerance and still not carrying out an attitude of tolerance. Keywords: pai teachers’ efforts, tolerant attitudes